Early Detection of Aluminum Toxicity on Bridelia monoica Merr. to Post Coal Mined Land in PT. Jorong Barutama Greston, South Kalimantan DETEKSI DINI KERACUNAN ALUMINIUM TANAMAN Bridelia monoica Merr. PADA TANAH PASCA TAMBANG BATU BARA PT. JORONG BARUTAMA - Yadi Setiadi; Fiona Citra Anira (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
High solubility of Aluminium (Al) and toxic on post coal mined land cause low level of growth plant. Soil analysisused to ensure toxic level, thus the plant growth failure can be minimized. On the other hand, soil analysis is timeconsuming and costly. A simple and effective method to detect the existence of Al in the soil is needed. Bridelia monoicais a dominant pioneer tree which grow around mine location. This plant can survive on the dry land with low fertility, hasmany utility and easily found around mining area. It is expected that B. monoica can be used as biologic indicator of Altoxicity. The aim of this research was to determine the B. monoica response to Al toxicity on the post coal mined land atPT. Jorong Barutama Greston. This research conducted at four different colours of soil (three colours from post coalmined and original soil as control) with three replication. The data observed were root length, shape of root, amount ofleaf, leaf colour, and dry weight. This research resulted Al toxicity can decrease root length, amount of leaf, and dryweight, and changing the root shape on B. monoica. The research concluded B. monoica can be used as biologicindicator of Al toxicity.Key words: Aluminium, Bridelia monoica, post coal mined soil